APLIKASI MOBILE BERBASIS CBIR UNTUK PENCARIAN PRODUK PONSEL PADA ONLINESHOP - Nickolas Cornelius Siantar; Janson Hendryli; Dyah Erny Herwindiati (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
Phone or smartphone and online shop, there is something that cannot be separated with human. There are so many type of smartphones show up in the market that people are confused on which one to get on the online stores. Smartphones recognition is done by using the Histogram of Oriented Gradient to recognize shapes of phones, Color Quantization to recognize the color, and Local Binary Pattern to recognize texture of the phones. The output of the Feature Extractor is a feature vector which is used on the LVQ to process recognize through finding the smallest Euclidean Distance between the trained vectors. The result of this paper is an application that can recognize 16 phone types using the image with the accuracy of 9.6%